Exploring the Love Triangle of Authoritarianism, Populism, and COVID-19 Through Political Ecology: Time for a Break-Up? - Gonda, Noémi; Prado Córdova, José Pablo; Huybrechs, Frédéric; Van Hecken, Gert T. (Frontiers in Human Dynamics, 2022)
Authoritarian and populist regimes have used the coronavirus pandemic as another excuse to further push back on democracy. Through the lens of boundary-making, we discuss power processes in pandemic politics of three countries whose governments and power constellations rely on authoritarian and/or populist politics (Hungary, Nicaragua, and Guatemala). Our aim is to envision the conceptual and practical possibilities for breaking up the unhealthy love relationship amid pandemic politics, authoritarianism, and populism, and for ultimately dismantling all three. On the basis of secondary data, personal communications, and our lived experiences, we analyze pandemic politics in authoritarian and populist contexts, exploring their ambiguous and co-constitutive effects through three apparent contradictions. First, we discuss control, or the ways in which the framing of the pandemic by authoritarian and populist regimes as an emergency, a quasi-war situation, or an excuse for political opportunism entails an attempt to justify command-and-control policies upon public behavior, intimate daily life, and subject classification. However, these control measures also bring about contestation through self-quarantine calls, accountability-driven demands of epidemiological data, and/or counter-narratives. Second, we engage with the contradiction of knowledge, by pointing out how authoritarian knowledge politics regarding the pandemic are based on over-centralized decision-making processes, manipulation of epidemiological data, and the silencing of unauthorized voices. Simultaneously, these measures are challenged and resisted by counter-knowledge alternatives on pandemic data and the struggles for subaltern forms of knowledge that could make relevant contributions to public health. Third, we discuss the contradiction of subjectivation processes. Authoritarian regimes make extraordinary efforts to draw a line between those bodies and subjects that deserve state protection and those that do not. In this situation, multiple forms of exclusion intersect and are reinforced based on ethnic, political, national, and gender differences. The manipulation of emotions is crucial in these divisions, often creating “worthy” and “unworthy” subjects. This highlights interconnectedness among vulnerabilities and emphasizes how care and solidarity are important elements in defying authoritarian populism. Finally, we conclude by proposing strategies that would allow political ecology to support prospects of emancipation for social justice, desperately needed in a pandemic-prone foreseeable future.